Intrahepatic cholangiocarcinoma with a liver abscess due to hepatic actinomycosis - Tomoya Masuda; Kenta Kobashi; Ryoma Sugimoto; Hiroshi Ishii; Kensuke Tsunemitsu (Surgical Case Reports)
Abstract Background Liver tumors with liver abscesses are unusual and rarely reported. In particular, studies of intrahepatic cholangiocarcinoma with liver abscesses due to hepatic actinomycosis have not been reported. Case presentation A 73-year-old woman presented with swelling of the right hypochondrium. Computed tomography revealed a mass lesion that was continuous with the abdominal wall in the right lobe of the liver, suggesting a liver tumor invading the abdominal wall. A liver biopsy revealed intrahepatic cholangiocarcinoma with a liver abscess. The histopathological specimen contained bacterial masses of actinomycosis, and the cause of the liver abscess was determined to be hepatic actinomycosis. As a result of percutaneous drainage and antibiotic therapy, the part of the tumor attached to the abdominal wall disappeared; therefore, we assumed that most of the lesion was not cholangiocarcinoma but a liver abscess due to hepatic actinomycosis. Radical surgery for residual intrahepatic cholangiocarcinoma was performed after chemotherapy. Currently, the patient is alive without recurrence 2 years and 9 months after the operation. Conclusion We encountered a difficult-to-diagnose case of intrahepatic cholangiocarcinoma with a liver abscess due to hepatic actinomycosis. A needle biopsy allowed early diagnosis and percutaneous drainage was an effective treatment.